2016
DOI: 10.5500/wjt.v6.i2.347
|View full text |Cite
|
Sign up to set email alerts
|

Single-lung transplantation in emphysema: Retrospective study analyzing survival and waiting list mortality

Abstract: AIM:To performed remains a subject of debate and is the principal aim of the study. METHODS:This retrospective analysis included 73 patients with emphysema (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012). The outcomes of patients undergoing single-lung transplantation (SL) (n = 40) or double-lung transplant (DL) (n = 33) were compared in a Cox multivariate analysis to study the impact of the technique, postoperative complications and acute and chronic rejection on survival rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Consistent with prior work, a less restrictive preference was associated with a lower waiting list mortality rate and a higher transplantation rate in ILD (27,28). This study extends those findings to COPD (27,29,30). In short, we failed to find any substantial benefit to restricting patients with COPD or ILD to a bilateral transplant procedure.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with prior work, a less restrictive preference was associated with a lower waiting list mortality rate and a higher transplantation rate in ILD (27,28). This study extends those findings to COPD (27,29,30). In short, we failed to find any substantial benefit to restricting patients with COPD or ILD to a bilateral transplant procedure.…”
Section: Discussionsupporting
confidence: 88%
“…In another retrospective analysis conducted in Spain, it was demonstrated that single or double LTx had no impact on patient survival or complications. Implementing single LTx widely may alleviate donor-organ shortages and contribute to decreases in the morbidity and mortality of those patients on the national waiting list 24. Like other authors, we observed a predominance of males in the patients who underwent LTx in Spain 3.…”
Section: Discussionsupporting
confidence: 80%
“…Also, LVRS of the native lung at the same time of LuTX was reported in four patients were hyperinflation was to be expected (65)(66)(67). More recently ELVR was used to counteract NLH (51,65,(68)(69)(70)(71). All reports share a high rate of success in terms of improving lung function and reducing subjective breathlessness of patients affected by NLH.…”
Section: Lvr After or During Lutxmentioning
confidence: 99%
“…It is characterized by a radiographic evidence of graft compression and the decrease in lung function and exercise tolerance. Even if the first reports about LVRS as a method of treatment of this condition date back to 1997, only 11 case reports/case series with a total of 44 patients have been published so far (3,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Also, LVRS of the native lung at the same time of LuTX was reported in four patients were hyperinflation was to be expected (65)(66)(67).…”
Section: Lvr After or During Lutxmentioning
confidence: 99%
See 1 more Smart Citation